2013
DOI: 10.1261/rna.037200.112
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 facilitates accurate loading of precursor piRNAs into PIWI proteins

Abstract: PIWI-interacting RNAs (piRNAs) defend the genome against transposon activity in animal gonads. The Hsp90 chaperone machinery has been implicated in the piRNA pathway, but its exact role remains obscure. Here, we examined the effect of 17-N-allylamino-17-demethoxygeldanamycin (17-AAG), an Hsp90-specific inhibitor, on the piRNA pathway. In the silkworm ovary-derived BmN4 cells, 17-AAG treatment reduced the level of piRNAs and PIWI proteins. In vitro, the 5 ′ -nucleotide preference upon precursor piRNA loading wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 29 publications
4
44
0
Order By: Relevance
“…6). Additional proteins, such as GASZ, Tdrds, and chaperones, are likely components of the pICL complex (Olivieri et al 2012;Preall et al 2012;Xiol et al 2012;Izumi et al 2013). MOV10L1 does not interact with Tdrkh (Saxe et al 2013), which is required for 3 ′ end maturation.…”
Section: Discussionmentioning
confidence: 99%
“…6). Additional proteins, such as GASZ, Tdrds, and chaperones, are likely components of the pICL complex (Olivieri et al 2012;Preall et al 2012;Xiol et al 2012;Izumi et al 2013). MOV10L1 does not interact with Tdrkh (Saxe et al 2013), which is required for 3 ′ end maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has shown that Hsp90 and Hop interact with Piwi, mediate its phosphorylation, and silence phenotypic variations (32). Hsp90 mediates accurate loading of piRNA precursors into piRNA-binding proteins, and the absence of Hsp90 leads to inefficient piRNA biogenesis with a concurrent increase in TE mobility (33,34). Further, Shutdown (encoded by shu), a member of the FKBP family of immunophilins and an interacting partner of Hsp90, was shown to be required for both primary and secondary piRNA biogenesis (35,36).…”
mentioning
confidence: 99%
“…We and others have previously shown that the HSP90 machinery has a crucial role in the loading of Argonaute with small duplex RNAs and its activity is required for the stabilization of unloaded Ago1 and 2 [22,26]. In order to test if KHSRP and p72 regulate Ago2 that is not associated with miRNAs we knocked down these proteins in HeLa cells followed by a treatment with Geldanamycin (GD), a potent inhibitor of HSP90 activity.…”
Section: Khsrp and P72 Regulate The Level Of Unloaded Ago2mentioning
confidence: 99%